Effect of premium and commercial grade food to the growth of domestic cat, felis catus / Mohd Hafizuddin Ahmad - Ahmad, Mohd Hafizuddin (Faculty of Applied Sciences, 2017)
Domestic cat or scientifically named Felis catus is a mammal which is usually being kept at home as an indoor pet. Cats are carnivore in which they actually more prefer to consume smaller organisms. Nowadays, cat owners tend to feed their cats with dry food or kibbles and also wet food. This study on the effect of cats' growth will be beneficial to the cat owners by advising them to choose a good source of food for their cats. The objective of the study is to compare the best cat food between premium and commercial grade base on the weight and length of cats. Two kinds of cat food were used in this study which are Royal Canin for the premium grade and Prodiet for the commercial grade. Both group of cats showed increment in terms of weight and length for eight weeks. The mean is calculated for the range of weight and length for both group. For Royal Canin, the mean weight is μ=0.88 kg and the mean length is μ=7.33 cm. The average weight for Prodiet cat group is μ=0.52 kg and the average length is μ=6.5 cm. Royal Canin gives a higher rate of development in terms of weight and length of cats compare to the Prodiet.